(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In this work, a numerical model of laser texturing is considered. A finite element model of a representative sample of pure aluminum was created. The impact of a laser pulse was simulated, assuming a Gaussian volume distribution of the heat flux. Material properties are assumed to be constant and latent heat is accounted for. Results are obtained for the thermal field and the width of the vaporized zone, assuming that the crater is characterized by its maximum width. The numerical model was used to study the influence of pulse power density, reflection, focal diameter and pulse duration. The ablation threshold at different laser pulse durations was determinate.